Das zukünftige Verhältnis von Kapitalismus und Demokratie aus ökonomischer Sicht - Gebhard Kirchgässner (Center for Research in Economics, Management and the Arts (CREMA), 2015)
Whether democracy or capitalism should have normative priority depends on the philosophi- cal point of view but also how both are defined. The more rele vant perspective is, however, the positive one. Formally, politics dominate, bu t the economy often dominates de facto be- cause political decisions against interests of powerful economic players might cause high so- cietal costs. Since the downfall of the Iron Wall capitalism spread out much more than democ- racy. Future development might strongly depend on the development of the new authoritarian market economies: Can high growth continue wh ile political rights are largely suppressed, or do they have to concede more and more to democratic rights in order to ensure further eco- nomic growth? One would like to see the latter one, but this is by no means sure.
Keywords: H11; O10; 330; Capitalism; Democracy; Economic Development; Market Economy